2021
DOI: 10.3390/v13091724
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Epidemiological Features of Norovirus Infections in Brazil, 2017–2018

Abstract: Noroviruses are considered an important cause of acute gastroenteritis (AGE) across all age groups. Here, we investigated the incidence of norovirus, genotypes circulation, and norovirus shedding in AGE stool samples from outpatients in Brazil. During a two-year period, 1546 AGE stool samples from ten Brazilian states were analyzed by RT-qPCR to detect and quantify GI and GII noroviruses. Positive samples were genotyped by dual sequencing using the ORF1/2 junction region. Overall, we detected norovirus in 32.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 81 publications
7
12
0
Order By: Relevance
“…A high co-detection rate (30%) of HAdV with rotavirus or norovirus was found during the 3-year period of our study. Two previous studies from our group have demonstrated an overall detection rate of rotavirus and norovirus of 12% and 32%, respectively 27 , 28 . Given these high detection rates along with the exposure to multiple viruses at similar times increase the likelihood of multiple infections within a short window of time in the same host 54 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A high co-detection rate (30%) of HAdV with rotavirus or norovirus was found during the 3-year period of our study. Two previous studies from our group have demonstrated an overall detection rate of rotavirus and norovirus of 12% and 32%, respectively 27 , 28 . Given these high detection rates along with the exposure to multiple viruses at similar times increase the likelihood of multiple infections within a short window of time in the same host 54 .…”
Section: Discussionmentioning
confidence: 64%
“…In Brazil, the rotavirus vaccine (RV1, Rotarix) was implemented into the National Immunization Program in 2006, and rotavirus-associated infections, hospitalizations and deaths has been declining substantially 26 . Two previous studies from our group have recently demonstrated the epidemiological features of rotavirus and the high incidence and molecular epidemiology of norovirus from AGE cases in Brazil 27 , 28 . There are few studies in Brazil and elsewhere in regards to HAdV incidence, epidemiology and molecular characterization, especially in the post-rotavirus vaccine era.…”
Section: Introductionmentioning
confidence: 78%
“…These results are in agreement with those of recent studies conducted in Argentina and Latin America through both active and passive surveillance programs. 13,[16][17][18]30 We detected NV cases throughout the year, with higher rates during warmer and colder months. This seasonal pattern differs from other studies describing a single winter peak.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recent studies in developing countries have described the presence of NV accounted for 15%-30% of sporadic acute diarrheal episodes in both outpatient and hospital settings. 4,7,[16][17][18] NVs can be classified into genogroups based on complete VP1 amino acid sequences, of which GI and GII predominate in humans. Each genogroup can be further divided into genotypes based on nucleotide sequences of the capsid and polymerase regions.…”
mentioning
confidence: 99%
“…In the United States, >99% of all norovirus outbreaks are caused by GI and GII viruses (5); most outbreaks are associated with GII.4 Sydney (4). Globally, norovirus GIX has been detected less frequently and has not been associated historically with large outbreaks (5)(6)(7)(8)(9)(10). During 2009-2016, two norovirus GIX outbreaks were reported to CaliciNet, the US norovirus surveillance network (5,10).…”
mentioning
confidence: 99%